(3JCgjd GdZQjHs - (3GHf MLI GdMehj , CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdGRQGQj, Jbj GdOjf GHf MLg,J (B837 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3aEf ZQjH GdCOH bO eRbg GdTJGJ GjOi SHG , hfXeg HYO JCgjd ZQjHg ai CSdGc GdZQHG , hbO gRJfi MejI GdCOH Edi de Tedg ,hGLJeGYg HGdfSjH ef Cgdg , hbO SejJg JCgjd GdZQjH s
(3BNQgG (B:s
(3EPG cfJ ai OGQ hMGhdJ JQcgG aOYgG hajgG Ef QLYJ eYGO s
(3GfXQ JCgjd GdZQjH ddfhGMi HGdLRGA Gdhd HQbe (B107 (3COHs
(3fSNI NRGFfjI cJHJ dbGVi GdbVGI bWH GdOjf GdCNjVQis
(3hHgG ChQGb cKjQI CNJQbgG GdMHQ aWeSgG JeGekGs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs